Aberrant internal carotid artery in the middle ear: the duplication variant. Issue 4 (20th April 2019) - Anagiotos, Andreas; Kazantzi, Maria; Tapis, Marios
Abstract : Vascular variants concerning the internal carotid artery (ICA) at the skull base level are rare. Correct workup and diagnosis in case of suspicion of such a variant are important as it mimics glomus tumours and could complicate myringotomy or middle ear surgery. We report a case of a 39-year-old woman presented with a 6-month history of right pulsatile tinnitus and aural fullness. Ear microscopy examination revealed a pale red pulsatile mass anterior to the umbo. Radiological assessment using CT and MRI/magnetic resonance angiography confirmed the diagnosis of an aberrant ICA. Interestingly, a duplication of the ICA was demonstrated, in which the enlarged inferior tympanic artery presented as the aberrant ICA, whereas a narrower collateral hypoplastic native ICA was also present. A conservative approach with regular follow-up appointments was recommended.